Differentiating Takotsubo cardiomyopathy from ST-segment elevation myocardial infarction. Issue 4 (July 2019) - Asher, Elad; Odeh, Qasim; Sabbag, Avi; Goldkorn, Ronen; Elian, Dan; Ben Zekry, Sagit; Peled, Yael; Abu-Much, Arsalan; Mazin, Israel; Beigel, Roy; Matetzky, Shlomi; ,
Background: Takotsubo cardiomyopathy affects between 1.7% and 2.2% of patients hospitalized with suspected acute coronary syndromes. Characterized by chest pain, electrocardiogram changes, and transient left ventricular apical wall motion abnormality, it is under-recognized and often misdiagnosed. Objectives: In order to better differentiate between St-segment myocardial infarction and Takotsubo cardiomyopathy, we developed a scoring system. Methods: Of the 82 patients enrolled with Takotsubo cardiomyopathy, 67 had ST-segment elevation on electrocardiogram and were compared with 79 ST-elevation myocardial infarction patients. A multi-variant logistic regression model was used to find factors independently associated with Takotsubo cardiomyopathy. The Platelets and Thrombosis in Sheba (PLATIS)-Takotsubo cardiomyopathy is based on a 10-point scoring system: stressful events (3), females (2), no history of diabetes mellitus (2), estimated left ventricular ejection fraction ≤ 40% on admission echo (1), positive troponin on admission (1), and no smoking (1). Patients with Takotsubo cardiomyopathy were older (66 ± 11 vs 60 ± 11 years, p < 0.001), predominantly female (90% vs 15%, p < 0.001), with a lower incidence of diabetes mellitus, dyslipidemia, and smoking. Nevertheless, in-hospital mortality was similar in both groups. Results: In a multivariate logistic regression analysis, the average Platelets and Thrombosis in Sheba-Takotsubo cardiomyopathy scoring was significantly higher in Takotsubo cardiomyopathy compared with ST-elevation myocardial infarction patients (8.35 ± 1.7 vs 3.42 ± 1.6, p < 0.001). With an overall score of ≥7, the receiver-operating characteristic curve was 0.82 with a sensitivity of 75% and a specificity of 89% (positive predictive value = 85% and negative predictive value = 80%). Conclusion: The Takotsubo cardiomyopathy scoring system is a simple, reliable tool that can assist in diagnosing and differentiating between patients with Takotsubo cardiomyopathy and those with ST-elevation myocardial infarction.